Virtual eye region: development of a realistic model to convey emotion. Issue 12 (December 2019) - Barrett, Simon; Weimer, Frederick; Cosmas, John
Abstract: The human eyes and their surrounding features are capable of conveying an array of emotional and social information through expressions. Producing virtual human eyes which are able to communicate these complex mental states continues to be a challenging research topic in computer graphics (CG) as subtle inaccuracies can be the difference between realistic and uncanny. With the recent emergence of virtual customer service agents, the demand for expressive virtual eyes is increasing. One essential question that remains to be answered is: Can virtual human eyes effectively transmit emotion? Through a combination of 3D scanning and manual hand modelling techniques, we developed an efficient pipeline to realise a virtual model of the human eye area that displays real-world characteristics. From this model eye expression renders of the six basic emotions, anger, disgust, fear, happiness, sadness and surprise were generated (Ekman et al., 1969). The perceptual quality of the model was evaluated by showing respondents from two age groups the six eye expressions renders and corresponding real-world photos. Respondents then judged which of the six emotions best described each image. Our findings indicate a clear relationship between the recognition levels for both photographic and virtual stimuli plus a significant level of emotional perception was found for the virtual eye expressions of sadness and anger. This research of human cognition and CG is a starting point for investigating the use of artificial human eye expressions as an effective research tool in the perceptual community. Abstract : Psychology; Eye expression; Virtual; Emotion; Computer-generated; 3D scanning.; Avatar; Human perception